اثر استخدام بعض الوسائل التعليمية وفق طريقة جيكسو في تعلم الاداء الفني لبعض انواع مهارة التهديف بكرة السلة للطلاب - صالح, المشرف: أ.م.د. زانا محمد محمد; ظاهر, الباحث: لاويست قاسم (Sulaimani Journal for Humanities, 2023)
The aims of the research are : - Identify the impact of using some educational means according to the Jiksaw method in learning the technical performance of some types of scoring skill in basketball for students. - Identify the impact of the educational curriculum followed in learning the technical performance of some types of scoring skill in basketball for students. - Identify the differences between the experimental and control groups in the dimensional tests of the variables studied. The researcher used the experimental approach by designing two equal experimental and control groups with pre- and post-test, while the research sample only consists of students of the first academic year in the faculty of educational sport - Koya University for the academic year (2021-2022), and the researcher used a number of devices, tools, means of collecting information, questionnaire, tests and measurements to reach the objectives of the study, then the researcher prepared the educational curriculum according to the method of Jiksaw, To process the data, the researcher used statistical means (arithmetic mean, standard deviation, Levin Test , percentage , T.Test for samples of equal number), and the researcher reached the following conclusions: 1 - The educational curriculum according to the method of Jiksaw using some educational means that was applied to the members of the experimental group had more effectiveness in learning the technical performance of some types of scoring skill in basketball. 2- The educational curriculum followed that was applied to the members of the control group had a positive impact on learning the technical performance of some types of scoring skill in basketball. 3- The experimental group, which applied the educational curriculum according to the Jiksaw method using some educational means, surpassed the control group, which used the method used in learning, the technical performance of some types of scoring skill in basketball.